1998
DOI: 10.1016/s0092-8674(00)81449-x
|View full text |Cite
|
Sign up to set email alerts
|

IHF Modulation of Tn10 Transposition: Sensory Transduction of Supercoiling Status via a Proposed Protein/DNA Molecular Spring

Abstract: Architectural protein IHF modulates Tn10 transposition in vitro. IHF stimulates transposon excision. Also, separately, IHF forces transposon end/target DNA interactions into a constrained pathway, "channeling," that yields only unknotted intratransposon inversion circles. Negative supercoiling influences both effects, differently. We infer that IHF is an architectural catalyst: it promotes initial transpososome assembly and is then ejected from the transpososome. IHF then rebinds, altering transpososome confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 28 publications
4
130
0
Order By: Relevance
“…hns12 clones 1-3 and clone 1 from the wild-type strain). The qualitative and quantitative changes in the STP species are indicative of a transpososome structure in which the transposon ends are less tightly constrained relative to the folded transpososome (Chalmers et al 1998). Furthermore, since these changes are dependent on a mutation in H-NS, the results support the idea that H-NS plays an important role in modulating the structure of the transpososome in vivo.…”
Section: H-ns Affects Transpososome Structure In Vivosupporting
confidence: 55%
See 3 more Smart Citations
“…hns12 clones 1-3 and clone 1 from the wild-type strain). The qualitative and quantitative changes in the STP species are indicative of a transpososome structure in which the transposon ends are less tightly constrained relative to the folded transpososome (Chalmers et al 1998). Furthermore, since these changes are dependent on a mutation in H-NS, the results support the idea that H-NS plays an important role in modulating the structure of the transpososome in vivo.…”
Section: H-ns Affects Transpososome Structure In Vivosupporting
confidence: 55%
“…The latter products are almost exclusively unknotted inversion circles (Benjamin and Kleckner 1989). These intratransposon events arise as a consequence of geometric and topological constraints imposed by DNA supercoiling and IHF binding to the outside ends of the transpososome (Chalmers et al 1998). If H-NS does influence the structure of the transpososome in vivo, as we have provided evidence for in vitro, then some mutant forms of H-NS might produce a different distribution of STPs.…”
Section: H-ns Affects Transpososome Structure In Vivomentioning
confidence: 71%
See 2 more Smart Citations
“…Physical and biochemical studies confirmed this conclusion and revealed substeps and mechanistic details (e.g., Bolland and Kleckner 1996;Sakai and Kleckner 1997), including work with the Haniford group identifying a hairpin intermediate, which linked the mechanism of transposition to that of immunoglobulin rearrangements (Kennedy et al 1998). We also showed that Tn10 transposition is regulated by the imposition and release of torsional mechanical stress within a small DNA loop at one end of the transposon, with interplay between a bend-inducing architectural protein (IHF) and cellular supercoiling (Chalmers et al 1998). With this study, we first put our toes into the water of chromosomes as mechanical objects.…”
Section: Tn10 Transpositionsupporting
confidence: 56%